Traditional Mawlid Tradition: Local Wisdom Amidst the Onslaught of Millennial Community Civilization - Ainun Isthifha Darma (Jurnal Ar Ro'is Mandalika (Armada), 2021)
Tradition in the frame of customs is one of the most important elements in a particular society—which in fact is a variance between one community group and another. Almost all islands of the archipelago have different cultural traditions, such as the traditional mawlid in the islands of West Nusa Tenggara, especially northern Lombok or better known as North Lombok. In the implementation of the traditional mawlid tradition in North Lombok Regency, the Bayan Village section is carried out by opening: collecting crops such as rice / grain, fruits and so on. Then in the evening it continued with a reassurance event opened by the women who became the opening. The tradition of traditional mawlid as a cultural property of the community (local wisdom) is a combination of local wisdom with Islamic teachings framed in a religious ritual as a form of worship and praise to the One God. Cultural clashes that occur seem to shift traditions that have been passed down for generations are tightly attached to the bayan community because of the shift in values that occur so that the stigma of the community in preserving it (read: traditional mawlid celebration) is challenged in today's millennial era. This Mawlid celebration can be said to be a reflection of religious psychology that supports cultural preservation born from community civilization, and still exists in the midst of the onslaught of modern society or in other words millennial society.